Given the system of equations:
![\begin{gathered} y=x^2+2x+6 \\ y=-x+4 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/k3jcfi8poyflsyfwzjqgixreon1y3gf521.png)
Using the substitution :
So,
![x^2+2x+6=-x+4](https://img.qammunity.org/2023/formulas/mathematics/college/5g2q9ko7qpclj6z1b6gg0symidaukhb3vb.png)
Solve for x:
![\begin{gathered} x^2+2x+6=-x+4 \\ x^2+2x+x+6-4=0 \\ x^2+3x+2=0 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5ki5wdly1d65f0yo9510khqwjlsl9j9t9x.png)
Factor the last equation :
![\begin{gathered} x^2+3x+2=0 \\ (x+1)(x+2)=0 \\ x+1=0,x+2=0 \\ x=-1\text{or x = -2} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/acf7azqh2x1937n0lz69j9t3tiwewxv3x4.png)
So, the answer is option A
The solutions are: x = -1 , -2
y = 5 , 6
As order pairs , the solution will be : ( -1 , 5 ) and ( -2 , 6 )
The following image represents the graphical solution of the system